The Effects of Using a Geometric Shaped Sponge on the Physiological Motion and Kinematics Variables to Perform the Front-Hand Somersault Skill - Mohammed Jasim Mohammed Al-Khalidi (Journal of Global Pharma Technology, 2017)
The study included a number of axes that concentrated on using the sponges in the learning process as supportive means towards learning this particular skill which is considered rather difficult. A certain type of sponges where used to learn each stage of this skill. These types were different in shape and size, considering the height and potential of the individual sample, in order to help the learners master this skill in the best way possible. The learning group was given a 4-weeks course to learn the front-hand somersault using these supportive techniques, two credits a week. After 4 weeks, the result of each group was collected and compared (The original and the experimental group). The statistical results showed that the experimental surpassed the original one.Keywords: Sponge Pieces, Physiological Motion, Kinematics Variables, Performance Learning.